Konsep Bimbingan Konseling Anak Usia Dini Serta Alternatif Medianya Melalui Permainan Tradisional - Frendi Fernando (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2020)
Guidance and counseling in early childhood institutions should not only be given to those who have problem behaviors, but must also be given to children who are in the process of growth and development. In early childhood, guidance and counseling is based on how to make the child's growth reach an optimal point, both physical motor, psychological and socio emotional. The process is mostly done by playing, singing, dancing and others. Traditional games can be used as a medium of guidance and counseling for early childhood. Types of traditional games are very good for children's development such as dexterity, creativity, social, and so on. In terms of benefits, traditional game is certainly very different from most modern games today, which do not use physical activity (silence) by staring at mobile screens and individualists, which of course results in the physical, and socio emotional development and physical growth of children not running optimally. For this reason, it is necessary to preserve the traditional game culture through creativity in order to preserve local wisdom as well as efforts to develop media for guidance and counseling for young children.